The Influence of Coworking Spaces on the Enhancement of Innovative Capacity- A Literature Review - Yildiz, Senem Kozaman Ayguen (KARE PUBL, 2024)
For about the last ten years, the concept of coworking space and its effects have been one of the spatial arrangements that have begun to be discussed scientifically. In practice, the effects of these spaces, which are preferred by many different types of users to work with changing world conditions, are discussed in various disciplines in social, economic, physical, and spatial terms. Some studies see them as potential innovation centers, enabling social interaction, collaboration, and information exchange between firms. In this study, to assess the existence of this contribution, articles obtained through a search of the Scopus database were examined through content analysis using the VOSViewer and MAXQDA programs. Although there is a general belief that coworking spaces have a positive impact on knowledge sharing, collaboration, and innovation, some studies claim that this relationship varies according to certain conditions and contexts. Evaluations focusing on the micro level suggest that approaches that emphasize individualism in Western countries with neoliberal policies undermine the culture of community and collaboration. Studies at the macro levels claim that innovative processes left to individuals and communities in coworking spaces can contribute to value creation, yet the sustainability of these structures, which are not fed by external resources, is threatened by the lock-in effect over time. Analyzing the relationship between coworking spaces and innovation using a holistic, multidisciplinary and mixed- methods approach with the example of developing countries will provide valuable contributions to the literature.
Keywords: Knowledge flow; collaboration; coworking spaces; literature review; innovation; ENTREPRENEURSHIP; KNOWLEDGE; WORKING; PLACES; CITY; Public Administration